Efforts to Improve Students' Learning Outcomes in Knowing Angels and Their Duties Through Make a Match Method at Grade IV SDN 01 Sitiung: Upaya Meningkatkan Hasil Belajar Siswa dalam Mengenal Malaikat dan Tugasnya Melalui Metode Make a Match di Kelas IV SDN 01 Sitiung - mulyani mulyani (Journal of Vocational Education and Information Technology (JVEIT), 2020)
This study is to answer the problem statement "Does applying the Make a match method improve student learning outcomes in recognizing angels and their assignments in class IV SDN 01 Sitiung?" This study uses a qualitative approach to the Classroom Action Research (CAR). The research subjects were grade IV students at SDN 01 Sitiung. Data collection techniques used in this study were (1) participant observation method because the teacher as a researcher simultaneously observed and was observed directly by colleagues who also observed the activeness of the teacher and students during the learning process. (2) the test method is used to determine student learning outcomes after working on the questions given at the end of learning in each cycle. The data in this study are divided into two types, namely quantitative data and qualitative data. Quantitative data were obtained to find the grade average and the percentage. The study was conducted in 2 cycles. Cycle 1 results in an average grade of 73 achieved by 11 students who finished out of 23 students. With only 48% completeness. Cycle II with an average grade of 86 achieved by 19 students who finished out of 23 students with completeness reached 83%. Based on these data with the application of the Make a Match method, cycles I and II can be seen that there is an increase in learning outcomes after the implementation of the Make a Match method.